Kredibilitas Sumber Ilmiah di Era Digital - Apriandi, Muhammad Mirwan; Boedi Maritasari, Donna; Maulida, Baiq Zil An’gina; Karmila, Ilma (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
A source is said to be credible if it can be trusted. Sometimes it is difficult to determine whether a credible source is trustworthy or not because some of the information presents false information as facts without evidence. Moreover, in today's digital era, we often have difficulty finding credible scientific sources, because the emergence of the internet, news websites, blogs and social media platforms have become increasingly dominant in disseminating information. So it confuses consumers in assessing its credibility. In the digital era, information is very easy to obtain, but this affects the credibility of the information, now it is very difficult to distinguish between what is right and what is wrong, so we need to know how to find credible sources of information such as searching for information in accredited journals or accredited sites such as Google Scholar. Where the site has met the standard criteria for evaluating scientific sources such as having an author, having accuracy, being up-to-date, and being objective.